2022
DOI: 10.1002/cam4.5120
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of rectal cancer identifies hallmarks of early‐onset patients and next‐generation treatment strategies

Abstract: Background The incidence of colorectal cancer is increasing among young adults and more rectal cancers are reported. This study aimed to identify the clinical features specific for early‐onset rectal cancer and provide insights on cancer management. Methods Early‐onset (<50 years) and late‐onset (≥50 years) rectal cancer patients from a referral tertiary care center (SYSU cohort) and Surveillance Epidemiology and End Results database (SEER cohort) were included to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…To determine the correlation between ALKBH5 expression and clinic‐pathological characteristics of CRC, a total of 201 CRC patients combined with their fresh frozen tumour specimens originating from the institutional database program of colorectal disease (IDPCD) at our institute were also included in this study. The IDPCD cohort integrated patient data, including demographic and clinic‐pathological characteristics and follow‐up data, which was described in previous publications 20–22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the correlation between ALKBH5 expression and clinic‐pathological characteristics of CRC, a total of 201 CRC patients combined with their fresh frozen tumour specimens originating from the institutional database program of colorectal disease (IDPCD) at our institute were also included in this study. The IDPCD cohort integrated patient data, including demographic and clinic‐pathological characteristics and follow‐up data, which was described in previous publications 20–22 …”
Section: Methodsmentioning
confidence: 99%
“…The IDPCD cohort integrated patient data, including demographic and clinic-pathological characteristics and follow-up data, which was described in previous publications. [20][21][22]…”
Section: Patients and Samplesmentioning
confidence: 99%
“…It is estimated that within 10 years, one in four rectal cancers will be in those under 50 years of age 9 . The clinical, pathological and epidemiologic landscapes of EOCRC are fundamentally distinct from CRC in those with late‐onset CRC (LOCRC) 10–12 . EOCRC is described most commonly in the distal colon and rectum 13,14 with more adverse histopathological features such as poor differentiation, mucosal and signet cell pathology relative to CRC in older adults 15–17 .…”
Section: Introductionmentioning
confidence: 99%
“…9 The clinical, pathological and epidemiologic landscapes of EOCRC are fundamentally distinct from CRC in those with late-onset CRC (LOCRC). [10][11][12] EOCRC is described most commonly in the distal colon and rectum 13,14 with more adverse histopathological features such as poor differentiation, mucosal and signet cell pathology relative to CRC in older adults. [15][16][17] Data reporting on the prognosis of EOCRC is sparse and controversial; several single-institution studies have indicated a poorer prognosis, [18][19][20] while others have found equivalent or higher survival rates compared to LOCRC.…”
Section: Introductionmentioning
confidence: 99%